COMPARATIVE OUTCOME OF OPEN VS ROBOTICS ASSISTED SURGERY IN HEPATOBILIARY MALIGNANCIES - Kailash Chand Sharma; Kamlesh Agarwal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This review presents a detailed comparison of open surgery and robotics-assisted surgery in the treatment of hepatobiliary malignancies. Conventional open surgery remains the standard of care in managing large complex tumors because it allows for visual, and palpation based intraoperative assessment of the resection margins and extent of tumor clearance crucial in achieving a R0 resection. But it is linked with increased risk of postoperative complications such as Surgical Site Infection, Wound dehiscence and hemorrhagic events and more hospital stay and longer time to recovery. On the other hand, robotics assisted surgery uses less invasive approaches that improve the accuracy, flexibility and visibility of surgeries using high-definition stereoscopic vision. This modality is linked with reduced intraoperative blood loss, decreased post-operative complications and shortened time for the recovery, because of the decreased inflammation processes and enhanced local tissue repair. At the same time, high costs of robotic systems and long years needed for the surgeon to master the system remain the major challenges that limit the application of robotic surgery. This review makes it clear that, though the oncological results of both surgical approaches are similar in terms of OS and DFS, open surgery is often chosen for extensive resections because of its effectiveness. The growth of robotics-assisted surgery is expected to increase over time due to the development of technologies that make the costs of surgeries less costly and more accessible. Further studies are necessary to determine the oncological outcome, including local recurrence and disease-free survival, as well as the quality of life of the patients. Therefore, the selection of the surgical approach should be personalized based on the patients and tumor characteristics and the resources available at the particular center.